Phase 1 Safety and Pharmacokinetics Study of MK-2048/Vicriviroc (MK-4176)/MK-2048A Intravaginal Rings. (4th October 2018) - Hoesley, Craig J; Chen, Beatrice A; Anderson, Peter L; Dezzutti, Charlene S; Strizki, Julie; Sprinkle, Carol; Heard, Faye; Bauermeister, Jose; Hall, Wayne; Jacobson, Cindy; Berthiaume, Jennifer; Mayo, Ashley; et al.
Abstract: Background: Vaginal rings (VR) containing antiretroviral (ARV) drugs can be utilized for prevention of human immunodeficiency virus (HIV) with potential for improved adherence compared to daily pills. Combination ARV VRs could improve efficacy. Methods: MTN-027, a single-blind, randomized, placebo-controlled trial in 48 women, evaluated VRs containing MK-2048 (30 mg) and vicriviroc (VCV, 182 mg), alone or in combination, and placebo used continuously for 28 days. Safety was assessed by recording adverse events. Drug concentrations were quantified in plasma, vaginal fluid, cervical tissue, and rectal fluid. Cervical tissue was utilized for ex vivo HIV inhibition analysis. Results: There was no difference in related genitourinary adverse events between treatment arms compared to placebo. VCV and MK-2048 released from single or combination VRs both achieved peak concentrations in vaginal fluids, which were substantially higher compared to plasma (200× for VCV, 30× for MK-2048) and rectal fluid. In an ex vivo challenge assay, the antiviral activity of VCV and/or MK-2048 was not correlated with tissue-associated drug concentrations. Most women (77%) were fully adherent to 28 days of continuous VR use and found the VR acceptable. Conclusions: VCV and/or MK-2048 containing VRs were safe and acceptable. Both VCV and MK-2048 were quantifiable in all matrixes tested with peak compartmental drug concentrations similar for single and combination drug VRs. Tissue-associated VCV and/or MK-2048 did not correlate with inhibition of HIV infection. These data highlight the need to assess adequacy of drug dosing in the VR and measuring genital tissue drug concentrations to develop more precise concentration-response relationships. Abstract : This study evaluated vaginal rings containing vicriviroc and MK-2048 alone or in combination. The rings were found to be safe and acceptable. Although both drugs were quantifiable in all matrixes tested, HIV inhibition was not demonstrated in cervical tissue.